Efek ekstrak etanol kelopak bunga rosella (hibiscus sabdariffa l.) Terhadap biofilm prevotella intermedia - Gracia Masola Sulle; Mikha Sundjojo (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: The prevalence of periodontal disease in Indonesia reaches 96,58%. Prevotella intermedia is an orange complex bacteria play an important role in periodontitis. One of the therapies for periodontitis disease is the use of antimicrobial mouthwash. Rosella flowers can be used for an alternative therapy for periodontal disease because Rosella flower had been widely used as herbal drink. Purpose: This study aims to find out how rosella flower ethanol extract adheres to prevotella intermedia biofilms. Methods: This research is a laboratory experimental study using the biofilm test method. Rosella flower petals were taken from Balitro in Bogor, West Java. This research was conducted at the FKG Usakti MiCore Laboratory. The ethanol extract of rosella petals was diluted to obtain concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.12% and 1.5%. The wellplate was incubated for 1 hour, 6 hours and 24 hours under anaerobic conditions then read the OD (optical density) using a microplate reader at a wavelength of 49nm.Results: The normality test shows normal data distribution (p>0.05). The ANOVA test showed a significant difference (p>0.05). Post-Hoc test showed significant differences between the concentrations of the ethanol extract of rosella calyx. Conclusion: The ethanol extract of rosella calyx has an effect on inhibiting the attachment of the prevotella intermedia biofilm.